9 - Connecting African Activism with Global Networks: ICTs and South African Social Movements: DOI: 10.4314/ad.v30i1.22218 - Wasserman, Herman (Africa Development, 2005)
In this article the potential of ICTs to amplify the work done by social movements and activists in South Africa will be explored. Against the background of new dis courses of Pan-African Unity such as those around the African Renaissance and the New Plan for African Development (Nepad), the use of ICTs by a South African activist group, the Treatment Action Campaign, will be investigated to establish how these communication technologies can embed local social movements within larger political and communicative networks both on the African continent and globally.